Interest toward entrepreneurship among bachelor students in Faculty of Agro Technology in Universiti Technologi MARA (UiTM) Jengka, Pahang / Syamimi Zahari - Zahari, Syamimi (2014)
This study was undertaken to explore the interest towards entrepreneurship among Universiti Teknologi MARA (UiTM) Jengka, Pahang students. The population for the study is bachelor students from faculty of Agro Technology. Using a questionnaire survey on the students of Agro Technology faculty, this study aims to examine whether the Agro Technology students have an interest toward entrepreneurship. It also examine whether entrepreneurship background, business involvement and entrepreneurship program variables influence the students to become entrepreneurs. Questionnaires was distributed to 106 students of Agro Technology faculty. Pearson Correlation Coefficient was conducted in this study to observe independent variables (business involvement, entrepreneurial background and entrepreneurship program). One of the variables have significant relationship with entrepreneurial interest. Independent Sample T-test is used to test on personal details (gender differences) of respondents in opposition to dependent variable (entrepreneurial interest).